2017
DOI: 10.18632/oncotarget.22242
|View full text |Cite
|
Sign up to set email alerts
|

The sexist behaviour of immune checkpoint inhibitors in cancer therapy?

Abstract: BackgroundImmune checkpoint inhibitors, targeting the molecules CTLA-4, PD-1 and PD-L1, showed efficacy against several type of cancers and are currently used in clinical practice. An important biological variable that influences innate and adaptive immunity is the sex, acting through genetic, hormonal and environmental factors. The overall differences between sexes could be crucial to evaluate the response to ICIs.Materials and methodsWe performed a meta-analysis of Phase II-III Clinical Trials published up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 65 publications
2
86
0
2
Order By: Relevance
“…Recent studies demonstrated that males derive more benefit in ICI vs. chemotherapy than females. [39][40][41] Here, we report that the ICI predictive biomarker TMB has a better separation effect in female than in male patients. These two findings actually do not contradict each other.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Recent studies demonstrated that males derive more benefit in ICI vs. chemotherapy than females. [39][40][41] Here, we report that the ICI predictive biomarker TMB has a better separation effect in female than in male patients. These two findings actually do not contradict each other.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, it has been shown through systematic meta-analysis that male patients derive more benefit in ICI versus standard chemotherapy when compared to female patients. [39][40][41] Overall, for both men and women, immunotherapy was more effective than the control, whether this was a placebo or another type of cancer drug. 39 Here we hypothesize that the biomarker for predicting immunotherapy response could also be separated based on the patients' sex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women mount more vigorous antibody‐ and cell‐mediated immune responses than men following either infection or vaccination . Also, women have a higher incidence of autoimmune diseases, and the onset of these conditions are common during the reproductive years, suggesting that the pathogenesis of irAEs could be influenced by sex hormones . Studies in patients with endometriosis have reported a higher rate of autoimmune conditions in these patients, strengthening the link between autoimmunity and sex hormones .…”
Section: Discussionmentioning
confidence: 99%
“…Five different meta‐analysis have been reported to investigate the efficacy of immune checkpoint inhibitors according to the sex of cancer patients . In the previous meta‐analysis conducted by Botticelli and colleagues, there was no significant improvement of overall survival in male cancer patients treated with anti‐PD‐1 or anti‐CTLA‐4 antibodies. No available data of OS data and PFS data was found in the stratified analysis of cancer type like NSCLC according to the sex.…”
Section: Discussionmentioning
confidence: 99%